Using a Mixed-method Approach to Develop a Transition Program for Young Adults With Inflammatory Bowel Disease. Issue 2 (February 2020) - Maddux, Michele H.; Drovetta, Megan; Hasenkamp, Rachel; Carpenter, Ellen; McCullough, Jennifer; Goyal, Alka; Bass, Julie
ABSTRACT: Background: Although transition guidelines have been specified in pediatric inflammatory bowel disease (IBD), few IBD centers implement these into standard care. We describe a mixed qualitative and quantitative process of developing a needs-based transition program for adolescents and young adults with IBD. Methods: We enrolled 29 adolescents with IBD, 8 young adults with IBD in adult care, 14 pediatric gastroenterologists, and 58 adult gastroenterologists to provide input into barriers to successful transition, essential patient competencies, and key targets of clinical intervention. Results: The availability and expertise of adult gastroenterologists in childhood-onset IBD were identified by pediatric providers as primary barriers to health care transfer. A medical summary containing pertinent health information was identified by adult providers as instrumental to assume patient care post transfer. Young adults with IBD identified self-advocacy, education on insurance basics, and peer mentoring as essential targets of transition support and preparation in pediatric care. Findings were used to develop educational materials, a portable medical summary, a referral database of adult gastroenterologists, and a young adult clinic geared towards transition planning. Conclusion: Involving key patient and provider stakeholders in the development of a transition program is aimed at ensuring that the individual needs of patients and their families are met. Collaboration between pediatric and adult providers is also intended to facilitate a seamless continuum from pediatric to adult health care services. Efforts to evaluate the impact of such programming on self-management in adult care are needed.